Integration Of Islamic Education In The Implementation Of Behaviorism Theory - Dita Puspitasari; Kurnia Bahnur; Rahmawati Yusuf; Saprin Saprin (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2025)
Behaviorism theory is a learning theory that is expressed through experiments on animals and emphasizes behavior, changes in attitudes based on the results of stimulus-response accompanied by reinforcement. The purpose of this study is to analyze more deeply related to how the integration of Islamic education in the application of behaviorism theory so that it can be used in learning, especially Islamic religious education. The type of research used is library research. The results of this study indicate that: 1) Behaviorism theory is in line with the goals of Islamic education in instilling knowledge through the formation of behavior with the repetition of Islamic nuanced habits that can be used in the learning process 2) Complementary components, especially in meeting the biological and spiritual needs of students and 3) The integration of Islamic education with behaviorism theory is said to be equivalent, because it can be linked to the existing explanations in Islamic education, especially the holy verses of the Qur'an, which include Connectionism, Classical, Operant Conditioning, and the theory of Clark Hull and its principles include the principle of consequences, attitude changes and stimulus-response so that it can be used in learning.